INFORMATION CRM SYSTEMS IN ORGANIZATIONAL AND MANAGEMENT ACTIVITIES OF TECHNICIANS-PROGRAMMERS - Kamalova, Г.Б; Vodolazkina, Н.А; Aklbekov, К.И (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Allocation of organizational and managerial activity as an independent type in the structure of the professional activity of a technician-programmer, including the implementation of such organizational and managerial functions as planning and teamwork, making and implementing managerial decisions, establishing and maintaining internal and external communications, evaluating and developing professional and career advancement, project management, will allow him to effectively organize activities, both his own and the division of the organization entrusted to him. One of the main organizational and managerial functions is the functions of customer relationship management. These tasks are implemented in CRM systems. To automate the organizational and management activities of specialists of various levels, including technicians-programmers, today, in the context of the rapid development of technology and technology, large-scale digitalization, it is advisable to use such information systems. Possessing high technical and functional capabilities, they allow to accumulate and quickly process huge volumes of various information, to make decisions based on this information adequately and quickly. However, ready-made CRM systems are mostly paid and overloaded with unnecessary functionality, since they are only one of the components of a giant corporate system. Practice shows that small companies are limited to the minimum required set of functions implemented in such CRM systems, so it is often easier to develop their own CRM systems for their processes. In this article the requirements for such systems of automation of organizational and management activities of technicians-programmers and its functional structure are describes.